Assessment of implant stability during various stages of healing placed immediately following extraction in an overdenture situation - Ashwin Thomas Koshy; T Aby Mathew; Nicholas Mathew; Angel Mary Joseph (Wolters Kluwer Medknow Publications, 2017)
To assess the implant stability during different stages of healing in an immediate loaded implant soon after extraction. A 73-year-old female came with a chief complaint of bad smell and irritation in her lower front gum region. On examination, she was found to be completely edentulous in the maxillary arch and partially edentulous in the mandibular arch with only the canines present bilaterally. The posterior mandibular ridge was severely resorbed and hence could not be treated with a conventional mandibular complete denture. Considering the age of the patient and the preference of only a single surgical visit, we decided to plan for a conventional maxillary denture against an implant supported mandibular overdenture with two implants placed immediately after extraction of canines. The stability of these implants was assessed during the early phases of healing with the help of a resonance frequency analysis method (RFA) using Osstell ISQ™. During the healing phase, implant stability quotient (ISQ) values decrease by 4-5 values after installation with the lowest values at the 1st week postplacement. Following this, the ISQ values increased steadily for all implants up to 16 weeks. No significant differences were noted over time. At placement, the mean ISQ values at 33 and 43 regions were 74 and 75.2, respectively. The mean lowest ISQ values recorded at the 1st week were 58.8 and 65.4, respectively. At 16 weeks, the mean ISQ values were 70.5 and 67.9, respectively. The survival of such immediately placed implants, which are later used as overdenture supported implants, are highly predictable when the surgical and prosthetic part is done meticulously. However, there needs future studies oriented to understand better the healing pattern of immediately placed implants in extraction sockets, which would guide the clinician with the optimal loading time.